The door marked Malaya - Crawford, Oliver (London : Hart-Davis, 1958)
Personal account of the author's experiences in Malaya and Singapore in 1954-55 while serving with the First Battalion, Somerset Light Infantry (Prince Albert's).
Keywords: Crawford, Oliver; Jungle warfare; Communism -- Malaysia -- Malaya; Malaya -- History -- Malayan Emergency, 1948-1960.